Geometric morphometric characterization of the Balkan alpine grasshopper genus Oropodisma Uvarov, 1942 (Orthoptera, Acrididae, Melanoplinae), with description of two new species - Marina Trillo; Joaquín Ortego (ZooKeys)
In this study, we employ a geometric morphometric approach to quantify morphological differences among taxa of the genus Oropodisma Uvarov,1942, a complex of alpine grasshoppers comprising several narrow endemic species distributed across different mountain ranges of the Balkan Peninsula. The genus was described by Uvarov in 1942 and currently includes 10 recognized species, primarily distinguished by subtle differences in the shape of the male phallus apex and furculae. Some populations from central Greece exhibit an uncertain taxonomic status, suggesting the possible existence of undescribed species. Quantitative morphological comparisons with specimens collected from the type localities of all currently recognized taxa revealed the presence of two new species in the Pindus Range, Greece: O. tzoumerkae sp. nov. from Mount Tzoumerka and O. agrafae sp. nov. from Mount Agrafa. Geometric morphometric analyses indicate that O. tymphrestosi and O. willemsei, which occur in adjacent mountain ranges from central Greece, do not exhibit statistically significant differences in the shapes of either the phallus apex or the furculae. This finding raises doubts about their current taxonomic status but may also reflect the limitations of geometric morphometric approaches in capturing subtle differences in the complex structures that characterize male genitalia. Overall, our analyses highlight the value of quantitative approaches in formally reassessing the taxonomic status of species complexes. The description of two new and geographically restricted species within Oropodisma further emphasizes the role of Mediterranean mountains as key centers of microgeographic speciation for alpine biotas.